An Assessment of Radiolucencies Associated with Second Molar Adjacent Impacted Third Molar in Left in Comparison to Right Mandible: An assessment of Radiolucencies - Shafique, Maha; Farrukh, Samra; Tajamal, Hafiz Zain Bin; Babary, Darab Fatima; Qasim, Amna; Butt, Hira (Pakistan Journal of Health Sciences, 2023)
Mandibular third molars are the most prevalently impacted teeth in the oral cavity. These partially impacted teeth in addition to being the root cause of pathologies in the third molar themselves also pose problems for their adjacent second molars. The second molars adjacent impacted third molars lead to the development of various pathologies that manifest themselves as radiolucencies on radiographic evaluation. Objective: To evaluate the radiolucencies of the left mandible's second molar next to the impacted third molar in comparison with right mandible. Methods: A cross-sectional and descriptive study was undertaken on patients visiting College of Dentistry, Sharif Medical and Dental College (SMDC). A total of 385 OPGs were assessed for the presence of radiolucencies in the second molars adjacent impacted mandibular third molars from December 2020 to February 2021. Results: The association between the availability of periapical radiolucencies (p≤0.001) and radiolucencies due to caries and external resorption in second molar in the right and left mandible (p≤0.001) was significant. Conclusion: It was seen that majority of the cases with periapical radiolucency in the right mandible also had them left mandible as well but most of the cases with caries and external resorption in the right mandible did not have them in left mandible as well.